Echocardiography‐defined pulmonary hypertension is an adverse prognostic factor for newly diagnosed multiple myeloma patients. (24th April 2022) - Jian, Yuan; Zhou, Huixing; Wang, Yidan; Zhang, Zhiyao; Yang, Guangzhong; Geng, Chuanying; Tian, Ying; Gao, Wen; Chen, Wenming
Abstract: Background: Pulmonary hypertension (PH) is a common but rarely recognized comorbidity of multiple myeloma (MM) patients, while its prognostic significance for MM has been rarely reported. Methods: We retrospectively analyzed the clinical characteristics and prognostic value of baseline echocardiography‐defined PH in 426 newly diagnosed MM (NDMM) patients. Results: Echocardiograph‐defined PH was found in 12.7% (54/426) of NDMM patients, associated with older age, anemia, and renal insufficiency, as well as severe diastolic dysfunction and higher BNP and NT‐pro‐BNP levels. Patients with PH presented with a higher prevalence of atrial fibrillation, while with a similar incidence of thrombosis compared with those without PH. Based on similar treatment regimens and autologous stem cell transplantation (ASCT) rates, patients without PH have deeper and better responses than those with PH ( p  = 0.002). With the remission of MM, 81.5% of PH was reversible, accompanied by improvement of right ventricular dysfunction and normalization of BNP/NT‐pro‐BNP levels, while could reoccur at MM relapse. Survival analysis revealed that PH was an adverse prognostic factor, associated with reduced progression‐free survival (PFS) (21 vs. 50 months, p  < 0.001) and overall survival (OS) (45 vs. 90 months, p  = 0.014). Multivariate analysis further verified that baseline PH was an independent predictor for shorter PFS and OS. Conclusion: In conclusion, echocardiography‐defined PH is an adverse prognostic indicator for MM patients and should be routinely evaluated in MM patients at diagnosis to make a precise prognosis. Abstract : Pulmonary hypertension (PH) is an adverse prognostic factor of progression‐free survival (PFS) and overall survival (OS) for newly diagnosed multiple myeloma patients.